Sociological, Psychological, Scientific and Technological Foundations in Designing Arabic Language Curriculum - Dinan El Haq Rahimahullah; Isop Syafei; Dadan Nugraha (UIN Sunan Gunung Djati Bandung, 2025)
To truly understand Arabic and its intricacies, effective and efficient Arabic language learning is necessary. To achieve effective and efficient Arabic learning, careful planning in the form of a curriculum is required. In teaching Arabic language, the curriculum is developed based on certain foundations. The purpose of this paper is to describe the foundations in designing an Arabic language curriculum. This paper focuses solely on the sociological, psychological, scientific, and technological foundations. This study uses qualitative data, which is presented in verbal form rather than in numbers. Data was collected using the literature review technique, namely by studying theories from various relevant sources. After collecting the data, it is presented in the discussion section. The findings of this paper reveal that there are many fundamental aspects to consider before designing an Arabic language curriculum. However, this paper specifically discusses the sociological, psychological, scientific, and technological aspects. The sociological aspect ensures that the curriculum is relevant to social needs. The psychological aspect helps in understanding the mental and emotional development of learners, so that Arabic teaching methods can be adapted to their age, interests, and abilities. Science serves as the foundation for selecting theories that support language skills, while technology facilitates the learning process. These aspects complement each other to create an effective and innovative Arabic language curriculum, so that Arabic learning is not only theoretical but also practical and contextual.